When Seeing Is Better than Doing: Preschoolers’ Transfer of STEM Skills Using Touchscreen Games - Schroeder, Elizabeth L.; Kirkorian, Heather L. (Frontiers in Psychology, 2016)
The purpose of this study was to examine the extent to which character familiarity and game interactivity moderate preschoolers’ learning and transfer from digital games. The games were based on a popular television show and designed to test skills related to STEM (science, technology, engineering, mathematics): numerical cognition (quantity of different sets) and knowledge of a biological concept (growth). Preschoolers (3.0-5.5 years, N = 44) were assigned to play one game and watch a recording of an experimenter playing the other game. Learning was assessed during pretest and posttest using screenshots from the game. Transfer was assessed using modified screenshots (near) and real-life objects (far). Familiarity was assessed by asking children to identify the television characters and program. Findings indicate that the effectiveness of the games varied by age and condition: Younger children learned from the quantity game, but only when they watched (rather than played) the game. They did not transfer this information in either condition. Conversely, older children learned from the growth game regardless of whether they played or watched. However, older children only demonstrated far transfer if they watched (rather than played) the growth game. Thus preschoolers may benefit more by watching a video than by playing a game if the game is cognitively demanding, perhaps because making decisions while playing the game increases cognitive load. Character familiarity did not predict learning, perhaps because there was little overlap between the lessons presented in the television program and game. Findings from the current study highlight the need for more research into educational games and applications designed for preschoolers in order to establish whether, how, and for whom screen media can be educationally valuable.